2014
DOI: 10.14257/ijast.2014.69.05
|View full text |Cite
|
Sign up to set email alerts
|

High Order Numerical Solution of a Volterra Integro - Differential Equation Arising in Oscillating Magnetic Fields using Variational Iteration Method

Abstract: In this paperwe have considered an integro-differential equation which describes the charged particle motion for certain configurations of oscillating magnetic fields. This equation contains variable coefficients with large expressions which complicate the application of any numerical method. We have used variational iteration method to find its numerical solution by developing MATHEMATICA modulae and solved a number of numerical examples. The results show high accuracy and efficiency ofour approach.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 6 publications
0
8
0
Order By: Relevance
“…In Figure 3(b) to show the convergence of the present method, we showed that by increasing the m the residual function decreases, where α = 0.50. Table 2 compares the obtained values of y(t) by the present method and the values given by Khan [18] (Legendre multi-wavelets) and Pathak [21] (Variational iteration method), it shows that the results obtained in the present method are more accurate. …”
Section: The Exact Solution Of This Equation Is Y(t) = T Sin(t) + Cos(t)mentioning
confidence: 72%
See 4 more Smart Citations
“…In Figure 3(b) to show the convergence of the present method, we showed that by increasing the m the residual function decreases, where α = 0.50. Table 2 compares the obtained values of y(t) by the present method and the values given by Khan [18] (Legendre multi-wavelets) and Pathak [21] (Variational iteration method), it shows that the results obtained in the present method are more accurate. …”
Section: The Exact Solution Of This Equation Is Y(t) = T Sin(t) + Cos(t)mentioning
confidence: 72%
“…Table 1 compares the error norm y − y m 2 by the present method and Dehghan [16] for examples 1-3. Table 3 compares the obtained values of y(t) by the present method and the values given by Khan [18] (Legendre multi-wavelets) and Pathak [21] (Variational iteration method), it shows that the results obtained in the present method are more accurate. The exact solution of this equation is y(t) = −t 3 + t 2 − 5t + 2.…”
Section: The Exact Solution Of This Equation Is Y(t) = T Sin(t) + Cos(t)mentioning
confidence: 72%
See 3 more Smart Citations